2018
DOI: 10.1021/acs.jafc.8b04549
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitroso-N-acetylcysteine Generates Less Carcinogenic N-Nitrosamines in Meat Products than Nitrite

Abstract: Nitrite reacts with secondary amines to form N-nitrosamines (N-NA), which lead to gastrointestinal cancers. The aim of this study was to compare nitrite with S-nitrosocysteine (Cys-SNO) and S-nitroso-N-acetylcysteine (NAC-SNO) with respect to N-NA formation, which was evaluated by determining the conversion of N-methylaniline to Nnitrosomethylaniline. Under neutral and acidic pH conditions, N-NA formation rate was nitrite > Cys-SNO > NAC-SNO. In the presence of copper or nucleophiles, NAC-SNO generated much le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(16 citation statements)
references
References 49 publications
2
13
0
1
Order By: Relevance
“…[24] Several approaches, including the addition of vitamin C or other antioxidants, have been applied to reduce nitrite content and nitrosamines formation. [6,24,25,48] Accordingly, our results imply a possible interaction between H 2 and vitamin C governing NR-mediated nitrite accumulation. It has been reported that H 2 could also be an antioxidant, not only selectively scavenging reactive oxygen species (ROS), [49] but also interacting with or modulating vitamin C metabolism.…”
Section: Participation Of Vitamin C In H 2 -Prevented Nitrite Accumulsupporting
confidence: 51%
See 3 more Smart Citations
“…[24] Several approaches, including the addition of vitamin C or other antioxidants, have been applied to reduce nitrite content and nitrosamines formation. [6,24,25,48] Accordingly, our results imply a possible interaction between H 2 and vitamin C governing NR-mediated nitrite accumulation. It has been reported that H 2 could also be an antioxidant, not only selectively scavenging reactive oxygen species (ROS), [49] but also interacting with or modulating vitamin C metabolism.…”
Section: Participation Of Vitamin C In H 2 -Prevented Nitrite Accumulsupporting
confidence: 51%
“…As a major source of antioxidant, vitamin C can react with many clinical health-risk factors, including nitrite. [6,24,25] To investigate the possible role of vitamin C in the above observed H 2prevention of nitrite accumulation, a time-course analysis of vitamin C level during tomato fruit storage, was determined by HPLC after treatment in the presence or absence of H 2 . Similar to the reduction of endogenous H 2 production (Figure 1c), decreased vitamin C levels were observed.…”
Section: Participation Of Vitamin C In H 2 -Prevented Nitrite Accumulmentioning
confidence: 99%
See 2 more Smart Citations
“…N-NA formation rate was nitrite > cys-NO > NAC-SNO, and the sum formation of N-NA by S-nitroso-Nacetylcysteine (NAC-SNO) in the product and stomach was 99% less than nitrite. 27 As NAC-SNO seems to be a good candidate molecule for the replacement of nitrite in meat products, the aim of the present study was to compare the inhibition of meat lipid peroxidation and antioxidant tone achieved by NAC-SNO to nitrite, in cured meat, during processing, storage, and digestion in stomach medium.…”
Section: ■ Introductionmentioning
confidence: 99%